2016
DOI: 10.1186/s12891-016-1124-6
|View full text |Cite
|
Sign up to set email alerts
|

Variability in conditioned pain modulation predicts response to NSAID treatment in patients with knee osteoarthritis

Abstract: BackgroundPatients with painful knee osteoarthritis (OA) demonstrate hyperalgesia and altered pain-modulatory responses. While some prior work has demonstrated cross-sectional associations between laboratory and clinical pain measures, it is unknown whether individual variability in quantitative sensory testing (QST) responses at baseline can prospectively predict analgesic treatment responses.MethodPatients with knee OA (n = 35) were compared on QST responses to a demographically-matched pain-free control gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
105
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(111 citation statements)
references
References 35 publications
6
105
0
Order By: Relevance
“…The function of CPM mechanisms is sometimes preserved in rheumatoid arthritis (up to 5 years after diagnosis) (Leffler, Kosek, Lerndal, Nordmark, & Hansson, 2002) and in osteoarthritis (OA), but impaired in temporomandibular joint (TMJ) arthralgia patients (Kothari et al, 2016) at sites with chronic pain but not at pain-free sites (Oono et al, 2014). Knee OA has sometimes been associated with reduced CPM and enhanced temporal summation of pain (Edwards et al, 2016), which predicts less pain relief after total knee replacement (Petersen, Graven-Nielsen, Simonsen, Laursen, & Arendt-Nielsen, 2016). Even though OA patients might not report a pain reduction following painful CS (provoked OA pain), magneto-encephalography and electroencephalography techniques indicate a decreased activation of the cingulate gyrus (Quante, Hille, Schofer, Lorenz, & Hauck, 2008).…”
Section: Clinical Relevance Of Pain Modulationmentioning
confidence: 99%
“…The function of CPM mechanisms is sometimes preserved in rheumatoid arthritis (up to 5 years after diagnosis) (Leffler, Kosek, Lerndal, Nordmark, & Hansson, 2002) and in osteoarthritis (OA), but impaired in temporomandibular joint (TMJ) arthralgia patients (Kothari et al, 2016) at sites with chronic pain but not at pain-free sites (Oono et al, 2014). Knee OA has sometimes been associated with reduced CPM and enhanced temporal summation of pain (Edwards et al, 2016), which predicts less pain relief after total knee replacement (Petersen, Graven-Nielsen, Simonsen, Laursen, & Arendt-Nielsen, 2016). Even though OA patients might not report a pain reduction following painful CS (provoked OA pain), magneto-encephalography and electroencephalography techniques indicate a decreased activation of the cingulate gyrus (Quante, Hille, Schofer, Lorenz, & Hauck, 2008).…”
Section: Clinical Relevance Of Pain Modulationmentioning
confidence: 99%
“…One study in surgical patients found QST measures, primarily lower electrical and heat pain thresholds, were associated with higher postoperative analgesic requirements 29. Recent studies suggest that QST measures can identify interindividual differences in particular mechanisms of pain perception, such as descending-inhibitory activity, which can explain responses to specific types of drugs 30,31. Our study demonstrates the feasibility of similarly measuring interindividual variation in ED patients.…”
Section: Discussionmentioning
confidence: 58%
“…In another open-label pilot study, both enhanced central sensitization (i.e., pain hypersensitivity) assessed using QST and decreased CPM at baseline predicted lower pain intensity 3 months after implantation of a spinal cord stimulator [31]. In contrast to the inverse association between basal CPM function and analgesia in response to these central nervous-system focused treatments, a recent open-label study of topical diclofenac for knee OA patients indicated that more robust pre-treatment CPM predicted better analgesic responses to this peripherally-applied NSAID [49]. …”
Section: Recommendationsmentioning
confidence: 99%
“…Furthermore, we are aware of only a small number of studies supporting the use of sensory testing as a predictor of treatment response for non-neuropathic pain conditions. In addition to those previously described in FM [76] and OA [49], one pharmacologic trial in low back pain appears to be ongoing [168], and several exploratory studies in migraine have linked a phenotype of persistent mechanical allodynia with a reduced analgesic response to triptans [30, 109], but these await replication in controlled studies.…”
Section: Recommendationsmentioning
confidence: 99%